1995
DOI: 10.1111/j.1439-0507.1995.tb00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Short therapy for tinea unguium with terbinafine: four different courses of treatment

Abstract: Terbinafine has partly solved the well-known problems in the treatment of dermatophyte nail infections. The aim of our study was to assess the effectiveness of very short treatment of dermatophyte nail infections with four different courses of terbinafine with or without chemical onycholysis. For this purpose, 60 patients, divided into four groups, were given different courses of treatment with oral terbinafine. Clinical, mycological and tolerability tests were performed before, during and after treatment. Cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…From these facts, it would be interesting to know whether or not pulse therapy with terbinafine is also effective. In this, some clinical trials have reported favorable results by intermittent dosing of terbinafine 4–8,12–14 …”
Section: Discussionmentioning
confidence: 99%
“…From these facts, it would be interesting to know whether or not pulse therapy with terbinafine is also effective. In this, some clinical trials have reported favorable results by intermittent dosing of terbinafine 4–8,12–14 …”
Section: Discussionmentioning
confidence: 99%
“…[115][116][117] The combination of daily terbinafi ne doses (250 mg) with chemical or mechanical removal of the nail offers little to no additional increase in effi cacy over terbinafi ne alone. 118,119 Similarly, only limited increases in effi cacy are observed when daily oral therapy is combined with adjunctive therapy including once-weekly topical amorolfi ne or once-daily topical ciclopirox. [120][121][122][123] In each study topical therapy appeared to confer slight improvements in response; however, limited sample sizes restrict their signifi cance and superiority over terbinafi ne alone could not be determined.…”
Section: Onychomycosismentioning
confidence: 99%
“…Intermittent dosing of terbinafine appeared to produce good treatment results in some clinical trials. 9,10,[14][15][16] The present study was designed to consider the pharmacokinetic properties of terbinafine and the standard dose in Japan.…”
Section: Discussionmentioning
confidence: 99%